(untitled) (London Journal of Engineering Research, 2024)
One of the first important steps in achieving informed data analysis is detection of outliers. Even in cases where the final values are often considered to be incorrect calculations or noise, they can still provide very important information in some cases. Therefore, it is very important to detect them before modeling and analysis. In this paper, we present a structured and comprehensive review of residual detection research. There are many different methods, hence the purpose of this article is to help the novice researcher to formulate his ideas and gain an easier understanding of the various lines of research in which research has been conducted on this topic.